Comparison between the dissolution profiles of prolonged-release ciprofloxacin tablets available in the Colombian market (2020)
Two 1,000 mg prolonged-release ciprofloxacin (CIP) tablets marketed in Colombia were compared for quality control tests and dissolution profile as established in the United States Pharmacopeia 42-NF 37 and the Food and Drug Administration guidance on dissolution testing. The dissolution profiles in three dissolution media (pH 1.2, 4.5, and 6.8) were examined and compared using mathematical methods with model-independent and model-dependent approaches. The results showed that the evaluated products met the pharmacopeial specifications. CIP exhibited poor dissolution in the pH 6.8 medium for both products, and the comparative analysis of dissolution profiles in pH 1.2 and 4.5 media indicated the in vitro similarity between the formulations with drug release adjusted to Weibull function kinetics. Both products can be considered pharmaceutically equivalent, and it is necessary to test their bioequivalence in an in vivo study in order to comply with the requirements established for modified-release formulations in most of the countries.